1997
DOI: 10.1016/s0022-5347(01)68240-5
|View full text |Cite
|
Sign up to set email alerts
|

Renal Stone Risk Assessment During Space Shuttle Flights

Abstract: Prepared for submission to d. Urologyhttps://ntrs.nasa.gov/search.jsp?R=19970003315 2018-05-11T07:02:30+00:00Z

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 17 publications
3
35
1
2
Order By: Relevance
“…Nutrient content of the in-flight foods were calculated from food chemical data generated by the Johnson Space Center Water and Food Analytical Laboratory. Net alkali absorption (NAE, mEq/24 h) was derived from urinary values as previously described [8, 12]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrient content of the in-flight foods were calculated from food chemical data generated by the Johnson Space Center Water and Food Analytical Laboratory. Net alkali absorption (NAE, mEq/24 h) was derived from urinary values as previously described [8, 12]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence from NASA and the Russian space program has shown that humans exposed to the microgravity environment of space have a greater risk for developing renal stones [6, 7, 8]. The majority of renal stones formed here on Earth are composed of calcium oxalate or a mixture of calcium oxalate and calcium phosphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the space environment, this risk of calculi formation is increased both in-and postflight by multiple metabolic factors (28,29). Osteoclastic activity is dramatically increased and grossly results in a one to one and a half percent loss of bone mass per month (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…This results in the hypercalciuria of microgravity. Additionally, hypocitraturia, low urine pH, a 10%-15% decrease in plasma volume and lower urine volume (12,28,29) resulting from the microgravity environment also predispose to stone formation. This has resulted in one in-flight urinary calculus and more then ten post-flight calculi in the combined Russian and US space flight experience.…”
Section: Discussionmentioning
confidence: 99%